1985
DOI: 10.1002/ijc.2910350602
|View full text |Cite
|
Sign up to set email alerts
|

Familial and environmental interactions in bladder cancer risk

Abstract: In a population-based study of 2,982 bladder cancer patients and 5,782 controls in 10 geographic areas of the United States which was designed to assess the role of environmental risk factors, information was also obtained on the history of urinary tract cancer in first-degree relatives. A family history of urinary tract cancer significantly elevated the risk of bladder cancer [relative risk (RR) = 1.45], with higher risks observed among patients under age 45. The risks of bladder cancer associated with positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 22 publications
6
37
1
2
Order By: Relevance
“…The largest case-control study (2900 cases; 5684 controls) demonstrated a RR = 1.5 (95% CI 1.2-1.8). [17] Familial risks tended to be higher among males (a finding not consistent among studies), younger probands (< age 45) and smokers. [17,20] No significant differences in risk emerged when case-control and cohort studies were compared.…”
Section: Case Reports Of Familial Tccutmentioning
confidence: 81%
See 3 more Smart Citations
“…The largest case-control study (2900 cases; 5684 controls) demonstrated a RR = 1.5 (95% CI 1.2-1.8). [17] Familial risks tended to be higher among males (a finding not consistent among studies), younger probands (< age 45) and smokers. [17,20] No significant differences in risk emerged when case-control and cohort studies were compared.…”
Section: Case Reports Of Familial Tccutmentioning
confidence: 81%
“…[17] Familial risks tended to be higher among males (a finding not consistent among studies), younger probands (< age 45) and smokers. [17,20] No significant differences in risk emerged when case-control and cohort studies were compared. Among the cohort studies, an analysis of the Mormon genealogy data base yielded a familial RR = 1.5 (95% CI 1.0-2.2); [16] the RR was 5.1 (95% CI 1.0-12.5) among probands <age 60.…”
Section: Case Reports Of Familial Tccutmentioning
confidence: 81%
See 2 more Smart Citations
“…Consistent with our results, which suggest a joint effect of smoking and family history, a 45% greater risk of bladder cancer among those who had a first-degree relative with cancer of the urinary tract was reported in a population-based case-control study that included 2982 patients with bladder cancer and a group of 5782 control participants (the United States National Bladder Cancer Study). 21 Moreover, the risk of bladder cancer was greatest among heavy cigarette smokers. The authors proposed incorporating both familial susceptibility and environmental factors into the risk assessment of bladder cancer in future studies.…”
Section: Discussionmentioning
confidence: 99%